1972
DOI: 10.1901/jeab.1972.17-405
|View full text |Cite
|
Sign up to set email alerts
|

AVERSIVE ASPECTS OF A FIXED‐INTERVAL SCHEDULE OF FOOD REINFORCEMENT1

Abstract: The key pecking of pigeons was reinforced according to a fixed-interval schedule of reinforcement. The pigeons were also given the opportunity to attack a restrained target pigeon. The attack rates during the sessions of fixed-interval reinforcement were higher than during the operant level sessions in four of the five pigeons. Most attack occurred during the post-reinforcement pause in key pecking. It was suggested that a fixed-interval schedule of positive reinforcement possesses aversive properties, the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 24 publications
4
36
0
Order By: Relevance
“…Terrace (1966) reported that birds showed "emotional" responses, such as wingflapping, during the extinction component of a multiple schedule, and Azrin et al (1966) found that pigeons would attack a target bird during extinction. Richards and Rilling (1972) obtained similar target-attack behavior in pigeons on an FI 90-sec schedule. Most of the attacks were recorded during the first half of an interreinforcement interval.…”
mentioning
confidence: 69%
“…Terrace (1966) reported that birds showed "emotional" responses, such as wingflapping, during the extinction component of a multiple schedule, and Azrin et al (1966) found that pigeons would attack a target bird during extinction. Richards and Rilling (1972) obtained similar target-attack behavior in pigeons on an FI 90-sec schedule. Most of the attacks were recorded during the first half of an interreinforcement interval.…”
mentioning
confidence: 69%
“…For example, Richards and Rilling (1972) found that attacks by the subject on a restrained target pigeon were higher under an FI schedule than prior to such training and that the attacks occurred most frequently during the early part of the interval. The authors suggested that the frequency of aggression be used as an index of aversiveness, although they obviously used the latter term in some sense more general than we have.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Brown and Flory (1972) showed that pigeons will respond to terminate the stimulus associated with an FI schedule; termination behavior typically occurred shortly after reinforcement, when the foregoing analysis suggests aversive stimuli occur. In addition, Richards and Rilling (1972) have shown that a pigeon is likely to attack another pigeon during the postreinforcement period on an FI schedule. Various "interim activities" (Staddon & Simmelhag, 1971), or adjunctive behaviors (Falk, 1972) on fixed IRI schedules, such as attack, escape, and general activity (Killeen, 1975), might be, at least in part, a function of aversive properties of the postreinforcement period.…”
Section: Discussionmentioning
confidence: 99%